INTENSITY OF THE 137Cs TRANSFER FROM SOIL TO TREE LAYER IN FOREST-BOG ECOSYSTEMS OF WESTERN POLYSSYA OF UKRAINE - Holovko, Oksana (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The range of researches was made on the specific of accumulation of 137Cs in forest-bog ecosystems of Western Polyssya of Ukraine. It was shown the absence of appreciable difference of accumulation of radionuclide in Scots pine tree in edaphic conditions of wet and humidic bors and humidic subor. Transfer factor of 137Cs for birch-tree components is increasing in the range of humidic suramen - humidic subor – wet bor – wet subor. The trees of European alder accumulated the radionuclide more intense in edaphic conditions of humidic suramen than in wet subor. It was made a conclusion that the largest value of transfer factor of 137Cs for assimilating organs and tissues of trees independently of edaphic conditions.